THE CODIFICATION OF HUMAN RIGHTS IN CANADA - St-Hilaire, Maxime; Laprise, Marie-Lou (Revue de droit de l'Université de Sherbrooke, 2012)
This article is an updated and slightly revised version of the national report submitted by the author to the International Academy of Comparative Law's Second Thematic Congress. The theme of the Congress, held from May 24th to 26th 2012 at the National Taiwan University, was “Codification”. The paper offers a systematic but brief account of the adjudicative protection of human rights, both collective and individual, in domestic law. Such an overview also provides the opportunity to identify a few trends in the development of the Canadian constitutional case law regarding human rights. Even if human rights had received quasi-constitutional protection several decades earlier, their codification as part of the supreme law of Canada in 1982 proved to be a significant step forward. This is particularly true for the fundamental freedoms of expression and religion, and for “legal rights.” The picture is more mixed, however, regarding democratic rights. Part II of the Constitution Act, 1982, relating to special rights of Aboriginal peoples, has had huge systemic repercussions. A notable source of concern is the Supreme Court’s continued hesitance on how to conceive of the relation between the Charter’s individual rights and freedoms and the special rights of Aboriginal peoples recognized in Part II of the C.A. 1982.